2021
DOI: 10.21834/ebpj.v6i17.2867
|View full text |Cite
|
Sign up to set email alerts
|

The Legal Implications of a Sale of Property by the Malaysian Developers under the Private Lease Scheme: In two minds?

Abstract: This paper aims to evaluate the legal implications of the private lease scheme (PLS) for a property sale by the developers. It mainly relies on statutes and court cases as its primary sources of information. PLS is selling a lease to purchasers by the developers. If purchasers were misled to believe a property is purchased and not the purchase of the lease, it is considered misrepresentation. An amendment to the law is timely to cater for a scheme that may address a different legal status of the purchaser. Aus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…The private lease schemes were once proposed to cater to the need for development strata schemes in Medini, Johor. The studies by Abu Bakar et al (2021) and Mohsin et al (2020) tell the ideology of creating a private lease scheme in Medini, but this concept was only a vision of how Medini's development should be. In reality, no legislation exists regarding the private lease scheme, and there was no actual implementation of the private lease concept.…”
Section: Literature Reviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…The private lease schemes were once proposed to cater to the need for development strata schemes in Medini, Johor. The studies by Abu Bakar et al (2021) and Mohsin et al (2020) tell the ideology of creating a private lease scheme in Medini, but this concept was only a vision of how Medini's development should be. In reality, no legislation exists regarding the private lease scheme, and there was no actual implementation of the private lease concept.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…Currently, Medini's development uses the same concept of strata lease scheme similar to Penang. Abu Bakar et al (2021) study elaborated on the legal framework under the National Land Code 1965; however, it was never mentioned how the National Land Code 1965 framework of lease works and connects with other legislation that supports the concept of private lease scheme. Both Bakar et al (2021) & Mohsin et al (2020 study suggested creating new laws for private lease schemes.…”
Section: Literature Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among scholars, there are differences in naming a lease scheme. Zainal et al (2022) defined it as strata lease scheme, Zamri (2019) and Abu Bakar et al (2021) called it a private lease scheme, while Mohsin et al (2020) and Zainuddin et al (2022) describe it as a strata private lease scheme. Different names but has the same requirement for registration; to ensure the dealing between the lessee and the lessor is secured.…”
Section: Moving Towards the Non-conventional Strata Schemementioning
confidence: 99%
“…Zainuddin et al (2022) describe a strata private lease scheme as a strata building that uses a private leasing mechanism in land dealing by Malaysian real estate industry players. Abu Bakar et al (2021) explain that the private lease scheme was proposed in the state of Johor to lease freehold land to buyers for the price paid by buyers. While Mohsin et al (2020) tells the strata private lease scheme mechanism in the state of Johor is a registration mechanism implemented on the stratified building.…”
Section: Moving Towards the Non-conventional Strata Schemementioning
confidence: 99%